Jovens [In] visíveis: trabalho e saberes nas trajetórias dos catadores e catadoras da Cooperativa de Recicláveis Santa Maria da cidade de Itapeva-SP - Souza, Tiago da Silva (2021)
This research analyzed the experiences related to work and school of the waste pickers, young and adults, from the Santa Maria Recyclable Cooperative, from the years in the municipal dump of Itapeva - São Paulo, to the present, on the cooperative's premises. With regard to the theoretical question, the research had the light of the most important youth research, trying to present a theme that could better understand poor youth and their precarious inclusion in the system, as is the case of waste pickers (Paulo Carrano, Juarez Dayrrel, Marilia Sposito and José de Souza Martins). As they are collectors of recyclable materials, important theoretical bases related to this world were presented (Rosalina Burgos and Antônio Bosi). Popular education was explored and reflected, seeking to understand the knowledge produced and its relationship with the formation of the Santa Maria Cooperative (Paulo Freire, Boaventura de Souza Santos, Jacob Lima, Lia Tiriba and Maria Clara Fisher). The research used the qualitative method, presenting the result through semi-structured interviews, which were given by young people and adults, being more specifically two women and four men. The interviews were conducted face-to-face between the months of October 2019 and February 2020. Through the interviews, it was possible to understand the meaning of the work for the men and women waste pickers, very connected to the work they did at the dump, a place of forgetfulness. On the other hand, the work presented itself as a central point of transformation in their lives, especially what they do today in the cooperative, which is linked to the knowledge that they produced in solidarity with others in the search for sustenance and for a more dignified life. With regard to school, exclusion from school emerges in an expressive way, but their dreams are still, in some way, related to the completion of studies.